2006
DOI: 10.5367/000000006777641615
|View full text |Cite
|
Sign up to set email alerts
|

From Business Development to Quality of Life

Abstract: Despite billions of euros of economic and infrastructural support, East Germany has experienced neither economic recovery in the form of the 'flourishing landscapes' promised by Helmut Kohl in 1989, nor a boom in innovation. Instead, the region is undergoing processes of accelerating demographic change: declining birth rates, selective migration-mainly of young women between 15 and 25-and as a result, an ageing population. The results include peripheralization of rural regions and marginalization of social gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…One stream of research indicated an indirect relationship between the concepts through perceived service quality and perceived value (Ogunmokun et al, 2020). Another stream of research establishes a direct link that leads PSI to customer welfare (Beetz & Neu, 2006;Edwards-Schachter et al, 2012). The findings of our study contribute to both the stream through the analysis from a health care perspective by suggesting that while patients perceived the service to be valuable and meaningful, they get the happiness that ensures the quality of life and welfare is enhanced.…”
Section: Theoretical Implicationssupporting
confidence: 51%
See 1 more Smart Citation
“…One stream of research indicated an indirect relationship between the concepts through perceived service quality and perceived value (Ogunmokun et al, 2020). Another stream of research establishes a direct link that leads PSI to customer welfare (Beetz & Neu, 2006;Edwards-Schachter et al, 2012). The findings of our study contribute to both the stream through the analysis from a health care perspective by suggesting that while patients perceived the service to be valuable and meaningful, they get the happiness that ensures the quality of life and welfare is enhanced.…”
Section: Theoretical Implicationssupporting
confidence: 51%
“…Despite this fact, extant research emphasizes the patient-centred approach where patients can manage the day-to-day health care responsibility (Barlow, Wright, Sheaby, Turner, & Hainsworth, 2002), and this approach is possible due to service innovation (Bouwman, de Vos, & Haaker, 2008). Furthermore, another stream of research considers innovation directly leads to customer welfare (Beetz & Neu, 2006;Edwards-Schachter, Matti, & Alcántara, 2012).…”
Section: Value Co-creation Perceived Service Innovation and Patient W...mentioning
confidence: 99%